Systematic Reviews of University Programs and Units - Harris, Walter E.; Holdaway, Edward A. (Canadian Journal of Higher Education, 1983)
Because universities in Canada, the U.S.A., and other Western countries are facing declining real income and increasing demands for greater accountability, they need to use resources more carefully and undertake planning activities more seriously. By obtaining information from reviews of academic and support units, universities are in a better position to meet these challenges. Most experts agree that reviews aimed at improvement of programs and activities are more successful when conducted under the authority of the university rather than an external agency. Attention needs to be paid to the establishment of an appropriate administrative mechanism that can maximize benefits relative to costs. This article describes the policies and procedures adopted in 1980 by The University of Alberta to allow for a continuous system of reviews of all academic and support units. Establishment of a President's Advisory Committee with a minimum of formal procedures has led to a successful system under which 51 units are now in various stages of the review process. The procedures used at The University of Alberta may be worthy of scrutiny by other universities contemplating such activity.